2019
DOI: 10.1002/bjs.11218
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neoadjuvant chemoradiation on preoperative pulmonary physiology, postoperative respiratory complications and quality of life in patients with oesophageal cancer

Abstract: Background It remains controversial whether neoadjuvant chemoradiation (nCRT) for oesophageal cancer influences operative morbidity, in particular pulmonary, and quality of life. This study combined clinical outcome data with systematic evaluation of pulmonary physiology to determine the impact of nCRT on pulmonary physiology and clinical outcomes in locally advanced oesophageal cancer. Methods Consecutive patients treated between 2010 and 2016 were included. Three‐dimensional conformal radiation was standard,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 45 publications
0
16
0
1
Order By: Relevance
“…CT-defined sarcopenia was conducted as described previously 17,18. Pulmonary physiology, including diffusion capacity for carbon monoxide, forced expiratory volume in first second, and forced vital capacity, was assessed at baseline and 1 month postneoadjuvant therapy as per guidelines 19,20…”
Section: Methodsmentioning
confidence: 99%
“…CT-defined sarcopenia was conducted as described previously 17,18. Pulmonary physiology, including diffusion capacity for carbon monoxide, forced expiratory volume in first second, and forced vital capacity, was assessed at baseline and 1 month postneoadjuvant therapy as per guidelines 19,20…”
Section: Methodsmentioning
confidence: 99%
“…25,26 In this context, we have recently reported that nCRT alters pulmonary physiology, in particular diffusion capacity (DLCO). 27 The observations from this study suggest that lung changes postoperatively in patients who had nCRT may not be infection related, and whether preoperative radiation and 1-lung anesthesia predispose to non-infective acute lung injury or consolidation requires further study.…”
Section: Discussionmentioning
confidence: 80%
“…Com base nesses achados e na literatura consultada, ratifica-se que os efeitos da quimioterapia sobre a função pulmonar são mais bem evidenciados meses após a conclusão do tratamento 27 . Apoiando esse pressuposto, o trabalho de Dietz et al 28 acompanhou um grupo de adultos sobreviventes ao câncer na infância e constatou que 25 anos após a terapia, os pacientes manifestavam tosse crônica, fibrose pulmonar, necessidade de suplementação de oxigênio e pneumonia.…”
Section: Discussionunclassified